Pengaruh Content Marketing, Live Streaming, Online Customer Review terhadap Minat Beli Konsumen pada Aplikasi Media Sosial Tiktok: (Studi Kasus Pelanggan TikTok Shop di Kabupaten Lamongan) - Yunita Dwi Editia; Indira Shofia Maulida; Moh. Muklis Sulaeman; Sabilar Rosyad (Jurnal Bintang Manajemen, 2025)
This study aims to analyze and test the effect of content marketing, live streaming, online customer reviews on consumer buying interest in the TikTok social media application in Lamongan Regency. This research uses quantitative methods. The population in this study were residents of Kec. Lamongan. The sampling method used in this study was purposive sampling of 100 respondents. The data analysis method used in this study is multiple linear regression analysis, with the help of SPSS version 26. The results of this study indicate that the variables of content marketing, live streaming, online customer review partially have a positive and significant effect on purchasing decisions. And the variables of content marketing, live streaming, online customer review simultaneously have a positive and significant effect on purchasing decisions. And the content marketing variable has the most dominant effect on consumer buying interest in the TikTok social media application in Lamongan Regency.